Policy Analysis of Sustainable Waste Management in DKI Jakarta: Public Health and Environmental Implications - Safri Safri (Administratio, 2024)
This study aims to analyze the sustainable waste management policy in DKI Jakarta within the framework of the Sustainable Development Goals (SDGs). This study identifies the challenges faced and evaluates the strategies and efforts implemented to improve the effectiveness of waste management in Jakarta.  Using a descriptive qualitative approach, it reviews policy documents, government reports, and in-depth interviews with 15 key informants from various agencies in Central Jakarta. Interviews were conducted with cleaners, residents, and scavengers, and field observations were made at waste t\ransfer stations, waste banks, and Integrated waste processing facility (TPST) Bantargebang. Document studies included regional regulations and performance reports from the DKI Jakarta Environmental Service. The results show that although the Jakarta Government has introduced initiatives such as waste sorting at source, recycling programs, and public awareness campaigns, these efforts are hampered by inadequate infrastructure, limited public participation, and insufficient funding. In addition, coordination between government agencies and the private sector is still less than optimal, which affects the overall impact of the policy. The results of this study conclude that Jakarta's waste management policy is still not fully aligned with the SDGs targets, due to several significant obstacles including lack of public awareness and suboptimal implementation of environmentally friendly technologies. The study emphasizes that Jakarta’s waste management faces significant challenges, particularly in terms of alignment with SDGs. However, the study offers actionable recommendations to improve cross-sector coordination, encourage the adoption of green technologies, and enhance public engagement. The findings can influence policy decisions by advocating for data-driven policy adjustments and better resource allocation. Future research should explore new technologies and compare Jakarta’s practices with leading cities to refine its waste management strategies and achieve more sustainable outcomes.